STUNTING MANAGEMENT IN ENREKANG REGENCY FROM THE PERSPECTIVE OF THE COLLABORATIVE GOVERNANCE REGIME - Muh Zhohirul Haq; Gita Susanti (Jurnal Administrasi Negara, 2026)
Stunting is a chronic nutritional problem with widespread impacts on the quality of human resources and sustainable development. One of the regions with the highest stunting rates is Enrekang Regency, South Sulawesi Province. Enrekang Regency has consistently recorded one of the highest stunting prevalence rates in South Sulawesi from year to year and has yet to achieve its prevalence reduction target. This study examines the implementation of the Collaborative Governance Regime (CGR) in managing stunting in Enrekang Regency. It aims to analyze the dynamics of multi-actor collaboration as well as the supporting and inhibiting factors affecting program effectiveness. This qualitative case study collected data through interviews and observations, which were then analyzed interactively and validated using triangulation techniques. The results indicate that inter-agency collaboration in Enrekang has been established through the three main dimensions of CGR: principled engagement, shared motivation, and capacity for joint action, which are manifested in integrated programs such as the Bapak/Bunda Asuh Anak Stunting (Stunting Children Foster Parents) initiative and cross-sectoral Convergence Actions. Since its inception, this collaboration has successfully reduced stunting rates from 28.50% (2019), 23.30% (2020), 21.50% (2021), 19.45% (2022), to 19.04% (2023). These results indicate that the dynamics of collaboration involving specific and sensitive interventions can increase public awareness in stunting management. However, obstacles were found in the form of budget constraints, government dominance in deliberative processes, and data collection challenges. Adaptation was carried out by focusing interventions on priority locus areas, optimizing the role of posyandu (integrated health post) cadres, and strengthening institutional coordination. It is concluded that strengthening fiscal capacity, involving non-governmental sectors, and improving the data collection system are key to the sustainability of collaborative stunting reduction at the regional level.